2017
DOI: 10.1038/s41467-017-02030-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical activation of OmpR drives acid and osmotic stress responses in single bacterial cells

Abstract: Unlike eukaryotes, bacteria undergo large changes in osmolality and cytoplasmic pH. It has been described that during acid stress, bacteria internal pH promptly acidifies, followed by recovery. Here, using pH imaging in single living cells, we show that following acid stress, bacteria maintain an acidic cytoplasm and the osmotic stress transcription factor OmpR is required for acidification. The activation of this response is non-canonical, involving a regulatory mechanism requiring the OmpR cognate kinase Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(177 citation statements)
references
References 51 publications
10
158
1
Order By: Relevance
“…This has been previously observed by others under different experimental conditions [7175], and also noticed in our global transcriptomic analyses in the presence of H 2 O 2 and HOCl (in preparation). It is possible that ArcAB may be noncanonically activated under certain metabolic conditions.…”
Section: Discussionsupporting
confidence: 90%
“…This has been previously observed by others under different experimental conditions [7175], and also noticed in our global transcriptomic analyses in the presence of H 2 O 2 and HOCl (in preparation). It is possible that ArcAB may be noncanonically activated under certain metabolic conditions.…”
Section: Discussionsupporting
confidence: 90%
“…OmpR binding and repression does not require phosphorylation (i.e., a D55A mutant is sufficient to repress the cadC/BA operon), although it does require the cognate HK EnvZ or the cytoplasmic domain of EnvZ, EnvZc. The assumption is that interaction of EnvZ with OmpR is sufficient to drive OmpR dimerization and DNA binding in the absence of phosphorylation (Chakraborty et al ., ). A similar mechanism appears to function with the closely related OmpR homologue CpxR, where studies in Legionella pneumophila showed that a D53A CpxR mutant was no longer capable of transcriptional activation, but was still competent for repression (Feldheim et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A particularly well-characterized TCS system is the EnvZ/OmpR system that is responsible for sensing changes in intracellular osmotic and acid environments, resulting in changes in the transcription profile (Chakraborty et al, 2015(Chakraborty et al, , 2017Wang et al, 2012). EnvZ is autophosphorylated (Aiba et al, 1989;Igo and Silhavy, 1988) on a conserved histidine residue, His 243 (Forst et al, 1987;Forst and Roberts, 1994), and osmolality enhances EnvZ autophosphorylation .…”
Section: Introductionmentioning
confidence: 99%